2015
DOI: 10.1111/anae.13347
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of ultrasound‐guided methods for brachial plexus blockade

Abstract: SummaryWe systematically reviewed 25 randomised controlled trials of ultrasound-guided brachial plexus blockade that recruited 1948 participants: either one approach vs another (axillary, infraclavicular or supraclavicular); or one injection vs multiple injections. There were no differences in the rates of successful blockade with approach, relative risk (95% CI): axillary vs infraclavicular, 1.0 (1.0-1.1), p = 0.97; axillary vs supraclavicular, 1.0 (1.0-1.1), p = 0.68; and infraclavicular vs supraclavicular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 51 publications
2
52
0
2
Order By: Relevance
“…The efficacy of these three techniques has been compared in several previous studies relative to a wide range of outcome variables [110]. A very recent systematic review of 25 randomized controlled trials of USG BP blockade found no differences in the rate of successful blockade with approach or with number of injections [11]. In the same review, only one randomized controlled trial was reported to have compared all three techniques in the same study [1, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of these three techniques has been compared in several previous studies relative to a wide range of outcome variables [110]. A very recent systematic review of 25 randomized controlled trials of USG BP blockade found no differences in the rate of successful blockade with approach or with number of injections [11]. In the same review, only one randomized controlled trial was reported to have compared all three techniques in the same study [1, 11].…”
Section: Introductionmentioning
confidence: 99%
“…A very recent systematic review of 25 randomized controlled trials of USG BP blockade found no differences in the rate of successful blockade with approach or with number of injections [11]. In the same review, only one randomized controlled trial was reported to have compared all three techniques in the same study [1, 11]. Tran et al [1] found no differences between groups with respect to total anesthesia-related time, success rate, and block-related pain scores.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a recent meta-analysis published by our group, the success rate of a supraclavicular block with a single injection was 86%. 1 We anticipated a 15% increase in the success rate with a retroclavicular approach. Assuming an alpha error of 0.05 and a power of 70%, we calculated that 48 patients per group were required to detect a statistically significant difference.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…A volume of 30 ml was chosen, as this is the most popular volume injected in most trials included in a recent meta-analysis that investigated ultrasound-guided supraclavicular or infraclavicular brachial plexus blocks. 1 After completion of the block, patients remained fully monitored until their transfer to the operating room.…”
Section: Ultrasound-guided Proceduresmentioning
confidence: 99%
See 1 more Smart Citation